Dampak lingkungan fisik dan kualitas pelayanan terhadap emosi pelanggan serta kepuasan konsumen sebagai variabel intervening - Ambo Sakka Hadmar (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2022)
This study examines the relationship model of the physical environment, service quality, satisfaction, and consumer emotions at a coffee shop in Jakarta. A quasi-experimental design was applied, with a sample of 60 respondents who were divided into two groups (treatment and control). The analysis results conclude that all identified variables have positive internal correlations. The results of the different tests showed significant differences in the rating of the physical environment, service quality, satisfaction, and emotion between the treatment and control groups, indicating that using unique designs and services in the room affected visitor attitudes. Finally, the physical environment and service quality have been shown to positively affect visitor satisfaction and emotions, and satisfaction also affects visitors' emotions.